2020
DOI: 10.1021/acsinfecdis.9b00412
|View full text |Cite
|
Sign up to set email alerts
|

Discovery of Compounds Inhibiting the ADP-Ribosyltransferase Activity of Pertussis Toxin

Abstract: Targeted pathogen-selective approach to drug development holds promise to minimize collateral damage to the beneficial microbiome. The AB5-topology pertussis toxin (PtxS1-S5) is a major virulence factor of Bordetella pertussis, the causative agent of the highly contagious respiratory disease whooping cough. Once internalized into the host cell, PtxS1 ADP-ribosylates α-subunits of the heterotrimeric Gαi-superfamily, thereby disrupting G-protein-coupled receptor signaling. Here, we report the discovery of the fi… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
29
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 32 publications
(37 citation statements)
references
References 54 publications
3
29
0
Order By: Relevance
“…No ADP-ribose signal was detected between 35 and 55 kDa markers if the reaction conditions lacked NAD + . As previously reported, 22 rPtxS1-wt and to lesser extent rPtxS1-Q127D/E129D had already become auto-ADP-ribosylated in the E. coli expression host as seen by the appearance of an ADP-ribose signal between 15 and 25 kDa markers. Based on these results, we concluded that the rPtxS1-wt ADP-ribosylated the rGαi target in the studied concentrations in the presence of NAD + .…”
Section: Resultssupporting
confidence: 81%
See 2 more Smart Citations
“…No ADP-ribose signal was detected between 35 and 55 kDa markers if the reaction conditions lacked NAD + . As previously reported, 22 rPtxS1-wt and to lesser extent rPtxS1-Q127D/E129D had already become auto-ADP-ribosylated in the E. coli expression host as seen by the appearance of an ADP-ribose signal between 15 and 25 kDa markers. Based on these results, we concluded that the rPtxS1-wt ADP-ribosylated the rGαi target in the studied concentrations in the presence of NAD + .…”
Section: Resultssupporting
confidence: 81%
“…Of note, rPtxS1 is an ADP-ribosyltransferase, which consumes NAD + also in the absence of its Gαi substrate, although to a much lower quantities. 22 In all assays, the NAD + concentration was fixed to 400 nM to ensure that the assay functionality is in the linear range determined by the manufacturer. The enzyme reaction was performed using 1 μM of substrates (PC10, PC15, and rGαi) and 200 nM of rPtxS1-wt.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Recombinant Gαi and recombinant PTS1 were expressed and purified as described earlier [ 46 ]. The used peptides α-defensin-1 and -5 as well as β-defensin-1 were purchased from PeptaNova (Sandhausen, Germany).…”
Section: Methodsmentioning
confidence: 99%
“…The Eu-probe was purified as described before, [31] and the concentration was determined using the DELFIA technique and a commercial EuCl 3 standard from PerkinElmer Life and Analytical Sciences, Wallac (Turku, Finland). The protein substrates, recombinant pertussis toxin (PTX), G protein alpha I subunit (Gαi) [33], human Ras GTPase-activating protein 1 (p120GAP) [34], wild type Kirsten RAt Sarcoma virus (KRAS, 2-188), human son of sevenless SOS1 catalytic domain (SOS cat , 564-1048) [35], and eukaryotic initiation factor 4A1 (eIF4A1) [32] were kind gifts from our collaborators. Malate dehydrogenase (MDH) was purchased from Roche (Basel, Switzerland).…”
Section: Materials Instrumentation and Assay Buffersmentioning
confidence: 99%